Tren penelitian kepemimpinan adaptif dalam pendidikan - Muhamad Mujari; Yuni Astuti; Priadi Surya (Curricula: Journal of Curriculum Development, 2026)
Adaptive leadership has attracted scholarly attention for several decades; however, comprehensive studies that systematically map its development remain limited. This study aims to examine the evolution, research trends, and theoretical and practical contributions of adaptive leadership, with particular focus on educational management. This study employs a Systematic Literature Review approach combined with bibliometric analysis. A total of 463 publications from 1989 to 2025 were retrieved from the Scopus database using the keyword "adaptive leadership". Data were collected on 21 May 2025 and analyzed using VOSviewer to map collaboration networks, thematic concentrations, and the evolution of scholarly discourse. The findings reveal a significant increase in research interest in adaptive leadership, particularly in response to rapid change, uncertainty, complex decision-making, and innovation within the context of digital transformation in education. This review identifies key attributes of effective adaptive leadership, including emotional intelligence, communication, empowerment, sense-making, resilience, navigational skills, collaboration, and proactive support for staff and student well-being. These findings contribute to the literature on educational leadership and offer practical implications for school governance in increasingly dynamic and complex educational environments.